Profile and risk factors of pre-XDR-TB and XDR-TB patients in a national reference hospital for Sumatra region of Indonesia - Sinulingga, Herison E.; Sinaga, Bintang YM.; Siagian, Parluhutan; Ashar, Taufik (Narra Sains Indonesia, 2023)
The low treatment rate, low treatment success rate and high mortality rate of patients with pre-extensively drug-resistant tuberculosis (pre-XDR-TB) and extensively drug-resistant TB (XDR-TB) need serious attention. The aim of this study was to describe the profiles of patients with pre-XDR-TB and XDR-TB cases and to determine associated risk factors of their incidence in Indonesia. A retrospective case-control study was conducted at H. Adam Malik General Hospital in Medan, North Sumatra of which all sensitive-drug TB (SD-TB), pre-XDR-TB, and XDR-TB patients aged 18 years or older treated between October 2019 to June 2022 were included. Chi-squared test or Kruskal Wallis test and multiple logistic regression were used to determine the risk factors associated with pre-XDR-TB and XDR-TB incidence. A total 16 patients of case group (15 pre-XDR-TB and one XDR-TB) and 116 SD-TB patients (control group) were included in the final analysis. Out of total patients within case group, 62.5% were male, 43.8% aged between 56–65 years, 62.5% graduated from high school or equivalent, and 25% were unemployed. The majority of patients had no comorbid (62.5%), had history of anti-TB treatment (93.8%), and had secondary resistance (93.8%). Multivariate analysis indicated that age (OR: 10.01; 95%CI: 1.49–66.91, p=0.018) and previous history of anti-TB treatment (OR: 216.25; 95%CI: 18.62–2511.60, p<0.001) were significantly associated with incidence of pre-XDR-TB and XDR-TB. This study highlights that having previous history of anti-TB treatment and older age are the predictors of the incidence of pre-XDR-TB and XDR-TB.